Gymnadenia conopsea (L.) R. Br.: A Systemic Review of the Ethnobotany, Phytochemistry, and Pharmacology of an Important Asian Folk Medicine - Shang, Xiaofei; Guo, Xiao; Liu, Yu; Pan, Hu; Miao, Xiaolou; Zhang, Jiyu (Frontiers in Pharmacology, 2017)
Gymnadenia conopsea (L.) R. Br. (Orchidaceae) is a perennial herbaceous orchid plant that grows widely throughout Europe and in temperate and subtropical zones of Asia. In China, its tuber has been used in traditional Chinese medicines, Tibetan medicines, Mongolian medicines and other ethnic medicines, and taken to treat numerous health conditions. The present paper provides a review of the traditional uses, phytochemistry, biological activities and toxicology to highlight the future prospects of the plant. More than 120 chemical compounds have been isolated, and the primary components are glucosides, dihydrostilbenes, phenanthrenes, aromatic compounds and other compounds. G. conopsea and its active constituents possess broad pharmacological properties, such as the tonifying effect, anti-oxidative activity, anti-viral activity, immunoregulatory, antianaphylaxis, antigastric ulcer, sedative and hypnotic activities, etc. However, overexploitation combined with the habitat destruction has resulted in the rapid decrease of the resources of this plant, and the sustainable use of G. conopsea is necessary to study. Meanwhile, the toxicity of this plant had not been comprehensively studied, and the active constituents and the mechanisms of action of the tuber were still unclear. Further studies on G. conopsea should lead to the development of scientific quality control and new drugs and therapies for various diseases; thus, its use and development require additional investigation.